Innovation and the Labor Market: Theory, Evidence and Challenges - Nicoletta Corrocher; Daniele Moschella; Jacopo Staccioli; Marco Vivarelli (Global Labor Organization (GLO), 2023)
This paper deals with the complex relationship between innovation and the labor market, analyzing the impact of new technological advancements on overall employment, skills and wages. After a critical review of the extant literature and the available empirical studies, novel evidence is presented on the distribution of labor-saving automation (namely robotics and AI), based on natural language processing of US patents. This mapping shows that both upstream high-tech providers and downstream users of new technologies - such as Boeing and Amazon - lead the underlying innovative effort.
Keywords: O33; 330; Innovation; Technological Change; Skills; Wages; Technological Unemployment